2017
DOI: 10.1002/ejic.201700875
|View full text |Cite
|
Sign up to set email alerts
|

A Bis(µ‐chlorido)‐Bridged Cobalt(II) Complex with Silyl‐Containing Schiff Base as a Catalyst Precursor in the Solvent‐Free Oxidation of Cyclohexane

Abstract: A new bis(μ-chlorido)-bridged cobalt(II) complex [Co 2 (μ-Cl) 2 (HL 2 ) 4 ][CoCl 4 ] (1), where HL 2 is a silyl-containing Schiff base, was synthesised. The structure of this compound was established by X-ray crystallography revealing a zwitterionic form adopted by the organic ligand. The temperature dependence of the magnetic susceptibility and the field dependence of the magnetisation indicate the presence of ferromagnetic interactions between paramagnetic d 7 cobalt(II) centres (S Co = 3/2). The exchange co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 62 publications
0
2
0
1
Order By: Relevance
“…However, many examples show that the optimal functional is not transferable from system to system. For example, it was observed that B3LYP [47,48] can give satisfactory results for copper [54][55][56][57] and cobalt [58,59] complexes, but is not the best functional for chromium [60], manganese [61] and iron [62] dimers. In these latter cases, TPSS0 [63,64], TPSSh [65] and M06 [66], respectively, are the best performing functionals to describe the experimental results.…”
Section: B Broken-symmetry Density Functional Theorymentioning
confidence: 99%
“…However, many examples show that the optimal functional is not transferable from system to system. For example, it was observed that B3LYP [47,48] can give satisfactory results for copper [54][55][56][57] and cobalt [58,59] complexes, but is not the best functional for chromium [60], manganese [61] and iron [62] dimers. In these latter cases, TPSS0 [63,64], TPSSh [65] and M06 [66], respectively, are the best performing functionals to describe the experimental results.…”
Section: B Broken-symmetry Density Functional Theorymentioning
confidence: 99%
“…Therefore, developing new highly efficient and robust heterogeneous catalysts for industrial-scale selective aerobic oxidation of cyclohexane is of great importance. In the last several years, various heterogeneous catalysts have been widely exploited for cyclohexane catalytic aerobic oxidation. For example, supported metalloporphyrins, transition metals with Schiff base ligands, , cobalt compounds, copper complexes, and metal nanoparticles have been developed to promote the cyclohexane conversion and the selectivity of KA oil under relatively mild and environmentally friendly reaction conditions. However, most of these catalyst systems either required high temperature/pressure or suffered from poor selectivity to KA oil.…”
Section: Introductionmentioning
confidence: 99%
“…Koordinasyon bileşikleri, bilim ve teknolojideki geniş uygulama alanları nedeniyle özel ilgi konusu olmuştur [1][2][3]. Özellikle Schiff baz ligandı içeren geçiş metali kompleksleri, çoğunlukla kataliz [4,5], kemosensörler [6,7], lüminesans malzemeler [8,9], enerji malzemeleri [10,11], manyetik-yapısal kimya [12,13] ve biyolojik alanlar [14][15][16][17] gibi çeşitli alanlardaki önemli uygulamaları nedeniyle dikkat çekmektedir. Schiff baz kompleksleri, kullanılan aldehit ve amine bağlı olarak, ligandlar için çok çeşitli olası yapılar oluşturabilmesi nedeniyle, yıllar içinde önemli ölçüde ilgi odağı olan konular arasında yer almıştır [18].…”
Section: Introductionunclassified